Paramedian Forehead Flap for Nasal Tip Reconstruction Related to Barbed Suture Infection - Ariani, Yuni; Wicaksono, Bambang (Lingkar Studi Bedah Plastik Foundation, 2022)
Introduction : The nasal tip abscess is a rare pathology that affects the soft tissue of the nasal tip, with risk of damaging the cartilaginous framework with the resulting alteration of the anatomy and function of the nose, if not treated properly.Case Presentation : A 22-year old female patient developed progressive defect with pain sensation at her nasal tip after bumping her nose 2 months ago and she admitted that she underwent a thread rhinoplasty 1 year ago. The reconstructive surgery was performed by excision of the ulcer, threads evacuation, and closing the defect with paramedian forehead flap procedure.Summary: In this case, the problem can be treated very well with the paramedian forehead flap procedure which is an excellent option for nose reconstruction.